Young Learners' Attitudes and Motivation towards Learning English in terms of Dörnyei’s Theory of Motivation - Demirbulak, Dilara; Zeyrek, Gülşah (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2022)
This study tries to explore young learners' attitudes and motivation towards learning English via Dörnyei’s motivational self-system. Designed as a qualitative study, the study employs interview schedules and an observation checklist that were adopted from Dörnyei and Csizer (2006) and a questionnaire designed by Ryan (2005). The data collection tools were, then, developed by the advisor and the researcher of the study upon expert opinion. The study was carried out with 57 primary school second-grade students from a state primary school in both face-to-face and online settings. The data were analyzed by thematic content analysis and coding via the Nvivo program. According to the results of the study, a positive learning environment and activities are significant factors that have an impact on young learners' attitudes and motivation to learn English. Regardless of the teaching environment, students' attitudes were mainly positive towards learning English and they were intrinsically motivated. This is especially important in countries where English proficiency is not as high as expected.